Respuesta :

Answer:

7.62

Step-by-step explanation:

We can use the distance formula

d = sqrt(  (x2-x1)^2 + ( y2- y1) ^2 )

  d = sqrt(  (1 - -2)^2 + ( 4 - -3) ^2 )

  d = sqrt(  (1 +2)^2 + ( 4 +3) ^2 )

d = sqrt(  (3)^2 + ( 7) ^2 )

d = sqrt( 9+49)

d = sqrt( 58)

7.615773106 or approximately 7.62

Answer:

7.62

Step-by-step explanation:

Ultimately, you want to create the two imaginary lines to form a triangle and to find the hypotenuse which is the distance between point A and point B.  From point B to the center of point A but not at it is 7 units and from there to point A, it is 3 units.  7^2 and 3^2 make up 49 and 9 which equals to 58.  Finally, square root that number and you will get 7.62 as your distance.